FY2019 China Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The country opinion survey in China assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in China perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in China on: (1) their views regarding the general environment in China; (2) their overall attitudes toward the WBG in China; (3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in China; and (4) their perceptions of the WBG’s future role in China.